(untitled) (The Pakistan Development Review, 1999)
Chris Roche defines impact assessment as “the systematic analysis of the lasting or significant changes—positive or negative, intended or not—in people’s lives brought about by a given action or series of actions” (p. 21). Consequently, the book intends to provide guidelines for ex-post assessments of the “impacts” development or other social sector projects have had on people’s lives. The reader learns about the various social impact assessment approaches and methods mainly through 11 case studies, which form the backbone of the book. These social impact assessments were carried out for ten development projects in developing countries—five of these are located in South Asia, including Pakistan—, and one social sector project in Europe. These projects vary considerably in scale, objectives, and the target group they purport to work for; and they were at different stages of the project cycle at the time the impact assessment was undertaken.